Landless children and child mobilizations in Brazil - Ramos, Márcia Mara; Aquino, Ligia Leão de (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This work focuses on children in the context of the fight for land spaces in Brazil, and on child mobilizations of the Landless Workers’ Movement (MTS, in its Portuguese acronym), which makes children visible and allows them to be present and play a leading role in the construction of the landless identity. As an educational experience in Latin America, educational practices with landless children have influenced grassroots movements associated with the Peasants’ Way by enabling greater participation of women in various scenarios, as well as the participation of children as historical subjects and subjects of law in the context of fight. For MTS, land, in its meaning of fight, is the possibility of reproducing human existence. There, children give meaning to the fight and are a part of it; likewise, it is the accomplishment of children from a working class. To rethink that place from an anti-hegemonic point of view requires the development of guided practice on the basis of political education. Such practice is related to socialist pedagogy and popular education in the organization of children in the countryside.